Effects of a grind & mix high nutrient density diet on starter pig performance - Blecha, Frank; Reddy, D.N.; Chitko-McKown, C.G.; Chengappa, M. M.; McVey, D.S.; Goodband, Robert D.; Nelssen, Jim L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Two 4-wk growth trials utilizing 520, 21-d old weanling pigs (22 ± 2 d and 13.7 lb) were conducted to evaluate either grind & mix (meal form) or pelleted high nutrient density diets on growth performance. One half of the pigs were fed a standard (20% dried whey and 10% plasma protein) high nutrient density diet (HNDD1) either in a pelleted or meal form. The other half received a high nutrient density diet (HNDD2; either pelleted or meal form) formulated with ingredients having greater flowability characteristics in order to determine if pelleting is necessary for pigs fed high nutrient density diets. Each trial was split into two identical phases, with Phase I being d 0 to 9 postweaning and Phase II being d 9 to 28 postweaning. Experimental diets were formulated to 1.5% lysine, .90% calcium, and .80% phosphorus and were fed only during Phase I. All pigs were fed a common diet (meal form) during Phase II formulated to 1.25% lysine containing 10% dried whey and 5% fish meal. There was an interaction between diet form and diet composition for ADG during Phase I (0-9 d) postweaning. Pigs fed meal-form HNDDI had a slightly higher ADG compared to pigs fed the same diet in a pelleted form. However, pigs fed pelleted HNDD2 grew slightly faster than pigs fed the meal-form of the same diet during Phase I. There were no interactions between diet form and composition for F/G or ADFI during Phase I or during the overall experiment. At d 9 postweaning, there was no difference in F/G between pigs fed HNDDI or HNDD2. However, pigs fed pelleted diets were more efficient than meal-fed pigs. Overall (d 0 to 28), pigs fed pelleted diets during Phase I, regardless of composition, were more efficient than pigs fed meal diets. Based on the results on this experiment, a high nutrient density diet can be fed in either a meal or pelleted form. Feed efficiency was 20% poorer for pigs fed the HNDD in the meal form. Therefore, a pelleted HNDD can cost up to 120% (excluding bagging expense) of mixing the same diet on-farm and be cost effective. Additional research is needed to understand the interaction between diet form and composition for ADG during Phase I and to improve diet flowability.
Keywords: Swine; Starter; Peformance; Process; Diet; Density